Business Development Through Business Legal Assistance: Pengembangan Bisnis Melalui Pendampingan Legalitas Usaha - Dewi Ayu Puspitasari; Rahman Amrullah Suwaidi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Tahfidzul Qur'an Al-Itqon Islamic Boarding School, one of the Islamic boarding schools in Jombang, East Java, will develop a food processing business unit. This Islamic boarding school has great potential to grow a sharia-based economic entity that supports financial independence. The biggest challenge faced is the lack of business legality, which limits access to a larger market and cooperation with strategic partners. This community service program aims to develop support for the legality of the Tahfidzul Qur'an Al-Itqon Islamic Boarding School as a strategic step to develop a more structured, legal and sustainable business. This program uses a qualitative descriptive approach with observation, interview and documentation methods. The mentoring process takes place in several stages including evaluating product needs, training and mentoring in managing business legality, for document processing requirements such as Business Identification Number (NIB) and Copyright IPR. The results of the activity show that mentoring for business legality has succeeded in increasing the professionalism of Islamic boarding school business management, opening wider market opportunities, increasing consumer trust, and partnerships with external parties. It can be concluded that mentoring in making business legality is an important factor in the professionalization of Islamic boarding schools.